Computer Self-Efficacy of Librarians and Users as Influencers of University Libraries Information System Security: Evidence from Nigeria - PhD., Benedict O. I. Okike & Niran Adetoro (COVENANT JOURNAL OF LIBRARY AND INFORMATION SCIENCE, 2019)
Librarians and their users interact with the library's information systems for different reasons. The need to protect information and information systems from unauthorized access, modification, data loss and destruction by librarians has become topical in recent times, hence this study. Using survey research design of the correlation type, three University libraries in the South-western Nigeria were purposively selected. Structured questionnaires for 48 librarians and 44,508 registered library users were used. Proportionate stratified random sampling technique for library users with Undergraduates, post graduates and staff as the basis for stratification was used. Total enumeration was used to capture all the librarians, total of 845 (95%) for library users and 42 (88%) for librarians were successfully completed and used for the study. Findings revealed that the librarians and library users had high computer self-efficacy levels related to information system security. Furthermore, computer self-efficacy of librarians significantly influence information systems security (β = .61, t= 4.86, p<.05) while computer self-efficacy of library users did not significantly influence information systems security (β = -.01, t= -.26, p>.05). The study concludes that these two groups have a strong belief in their abilities to use computers effectively to impact on the information system. The librarians’ belief is in the positive; the users appears to be for negative reasons. The study recommends very high level of computer and other technologies efficacy for librarians, regular training and retraining while users should be re-orientated to the realities and benefits of secured information systems.